Identifying ESG Indicators in the Context of Bank Customer Credit Assessment - Aghaei, Vahid; Seiedkhani, Reza; Mohammadipour, Rahmatollah; Feizollahi, Sadegh; Moradpour , Mojtaba (Business, Marketing, and Finance Open, 2024)
This study identifies ESG indicators in the context of bank customer credit assessment. The statistical population of this qualitative research consists of experienced university professors, researchers, and academic professionals, as well as senior, middle, and operational bank managers who possess sufficient knowledge and experience regarding the credit rating of applicants for bank facilities. Direct interviews were conducted with them. In this stage, interviews were conducted using the snowball sampling method until theoretical saturation was achieved. Thematic analysis led to the identification of eight key environmental criteria (sustainable practices, climate change initiatives, resource efficiency, pollution control, biodiversity conservation, green financing, adoption of renewable energy, and supply chain responsibility), eight key social criteria (community engagement, employee well-being, human rights, customer relations, diversity and inclusion, social impact investment, labor rights, and corporate ethics), and nine key governance criteria (corporate governance, transparency and accountability, risk management, ethical leadership, regulatory compliance, stakeholder engagement, board diversity, audit and oversight, environmental reporting, and anti-corruption measures).